2011
DOI: 10.1186/1471-2172-12-65
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine expression during early and late phase of acute Puumala hantavirus infection

Abstract: BackgroundHantaviruses of the family Bunyaviridae are emerging zoonotic pathogens which cause hemorrhagic fever with renal syndrome (HFRS) in the Old World and hantavirus pulmonary syndrome (HPS) in the New World. An immune-mediated pathogenesis is discussed for both syndromes. The aim of our study was to investigate cytokine expression during the course of acute Puumala hantavirus infection.ResultsWe retrospectively studied 64 patients hospitalised with acute Puumala hantavirus infection in 2010 during a hant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
54
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 42 publications
10
54
0
Order By: Relevance
“…The migration of mononuclear immune effector cells is governed by a specific set of chemokines including CXCL10 and CCL2 [21,22]; therefore, we also included these cytokines in our study. Consistent with previous reports [23,24], we observed elevated levels of TNF-α and IL-1β in Hantavirusinfected subjects. TNF-α and IL-1β were significantly higher in the sera of subjects with the severe w/c form of NE compared with subjects with the severe and the moderate forms.…”
Section: Discussionsupporting
confidence: 95%
“…The migration of mononuclear immune effector cells is governed by a specific set of chemokines including CXCL10 and CCL2 [21,22]; therefore, we also included these cytokines in our study. Consistent with previous reports [23,24], we observed elevated levels of TNF-α and IL-1β in Hantavirusinfected subjects. TNF-α and IL-1β were significantly higher in the sera of subjects with the severe w/c form of NE compared with subjects with the severe and the moderate forms.…”
Section: Discussionsupporting
confidence: 95%
“…Several studies have shown that the severe form of NE is associated with elevated IL-6 [3335]. Since IL-6 upregulation could be associated with high serum triglycerides, it could be suggested that metabolic syndrome in NE cases may contribute to proinflammatory cytokine activation, particularly IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…In NE patients the disease severity is characterized by elevated pro-inflammatory cytokines interleukin-6 and tumour necrosis factor-α, but low immunosuppressive transforming growth factor-β 1 levels. The upregulation of transforming growth factor-β 1 in the late phase of acute PUUV infection suggests a protective immunoregulatory role [141]. In NE patients cytotoxic T cells may contribute to the capillary damage via immunopathology, also by increased concentrations of nitric oxide and tumour necrosis factor-α [142,143].…”
Section: Hantavirus Pathogenesismentioning
confidence: 99%